(untitled) (Medico Legal Update, 2020)
Death of humans is often investigated for the causes, in case of crime (such as Murder), accident or disease that may continue to kill other humans. Deathoccurs due to natural causes or unnatural causes. The study of profile of medicolegal autopsies help us in determining crime rate, accident and common diseases in that particular area and also helpful in preventing unnatural deaths, improving healthcare system and reflecting law and order situation of that area. The present study was based on retrospective analysis of the autopsies performed during the period of January 2018 to December 2018 in the Department of Forensic Medicine and Toxicology, Bundelkhand Medical College, Sagar (M.P).A total of 349 autopsies were conducted during this study period, of which majority of victims were male 195 (56%) cases. Age group of 21-30 years having maximum number i.e. 128 (36.7%) cases. Natural death accounted for 12 (3.4%) cases and unnatural death 323 (92.5%) cases. The major cause of death among unnatural deaths was burn in 116 (33.23%) cases, followed byroad traffic accident (RTA) in 106 (30.37%) cases and poisoning in 40 (11.46%) cases. Burn was the major cause of death in our study, this may be due to smoking, defective electrical wiring, defective kerosene stove bursts, attempted suicides by self-immolation, homicidal burns of young women by husband or in-laws (dowry deaths).